2021
DOI: 10.1038/s41746-021-00523-3
|View full text |Cite
|
Sign up to set email alerts
|

It’s complicated: characterizing the time-varying relationship between cell phone mobility and COVID-19 spread in the US

Abstract: Restricting in-person interactions is an important technique for limiting the spread of severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2). Although early research found strong associations between cell phone mobility and infection spread during the initial outbreaks in the United States, it is unclear whether this relationship persists across locations and time. We propose an interpretable statistical model to identify spatiotemporal variation in the association between mobility and infection rates.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 24 publications
(42 reference statements)
1
21
0
Order By: Relevance
“…27,28 Notably, the negative correlation between closeness centrality and infection rates remained evident throughout the entirety of the pandemic in Japan, contrasting with prior research that suggests mobility is only a reliable predictor of infection rates during early stages of the pandemic. 26,29,30 Notably, Okinawa, Osaka, and Tokyo were consistent outliers in these analyses. Though outliers did not appear to markedly affect the association between closeness and COVID-19 positivity, the increase in cases nationwide naturally led to increased transmission, especially among those prefectures with the most "closeness."…”
Section: Discussionmentioning
confidence: 52%
“…27,28 Notably, the negative correlation between closeness centrality and infection rates remained evident throughout the entirety of the pandemic in Japan, contrasting with prior research that suggests mobility is only a reliable predictor of infection rates during early stages of the pandemic. 26,29,30 Notably, Okinawa, Osaka, and Tokyo were consistent outliers in these analyses. Though outliers did not appear to markedly affect the association between closeness and COVID-19 positivity, the increase in cases nationwide naturally led to increased transmission, especially among those prefectures with the most "closeness."…”
Section: Discussionmentioning
confidence: 52%
“…We relied upon the data on the six weekly Google mobility measures in the 111-county database, covering the 106-week period from the week ending February 24, 2020, through the week ending February 28, 2022, to compute the first principal component as a summary measure of mobility [ 20 , 21 ]. This summary measure, which we refer to here as our mobility indicator , represents the linear combination of the six individual mobility categories that captures the largest fraction of the overall variance of the data [ 28 ].…”
Section: Methodsmentioning
confidence: 99%
“…Mobility is a multidimensional concept that has been variously gauged by such diverse measures as smartphone visits to bars and restaurants [18], traffic patterns [7], and television watching as a proxy for time spent at home [19]. Here, following the lead of two key papers [20,21], we employ the statistical technique of principal component analysis to collapse the six-dimensional Google Mobility Reports [22] into a single mobility indicator. Further adhering to a recent study of reported case incidence and hospitalization in relation to vaccination rates during the Delta surge [23], we restrict our analysis to the most populous counties in the United States, together comprising approximately 44% of the total U.S. population.…”
Section: Introductionmentioning
confidence: 99%
“…We relied upon the data on the six weekly Google mobility measures in the 111-county database, covering the 106-week period from the week ending February 24, 2020, through the week ending February 28, 2022, to compute the first principal component as a summary measure of mobility [23, 24]. This summary measure, which we refer to here as our mobility indicator , represents the linear combination of the six individual mobility categories that captures the largest fraction of the overall variance of the data [32].…”
Section: Methodsmentioning
confidence: 99%
“…Mobility is a multidimensional concept that has been variously gauged by such diverse measures as smartphone visits to bars and restaurants [21], traffic patterns [9], and television watching as a proxy for time spent at home [22]. Here, following the lead of two key papers [23, 24], we employ the statistical technique of principal component analysis to collapse the six-dimensional Google Mobility Reports [25] into a single mobility indicator. Further adhering to a recent study of reported case incidence and hospitalization in relation to vaccination rates during the Delta surge [26], we restrict our analysis to the most populous counties in the United States, together comprising approximately 44 percent of the total U.S. population.…”
Section: Introductionmentioning
confidence: 99%